Manajemen Sarana dan Prasarana Pendidikan Pondok Pesantren: Studi Kasus Pondok Pesantren An Nawawi Berjan Purworejo - Muhlil Musolin (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
The background of the research is the availability of facilities and infrastructure to make all who live in boarding schools feel comfortable so they can carry out teaching and learning activities comfortably in boarding schools. Comfort in teaching and learning really determines the success of the educational process in Islamic boarding schools. This research uses a descriptive qualitative approach. It was held at the Pondok Pesantren Putra An Nawawi Berjan Purworejo. The data sources of this research are the documentation of the Islamic boarding school in the form of a book on the accountability report of the boarding school administrator of the son of An Nawawi Berjan Purworejo. Data collection method is documentation. Data analysis is done by examining existing data, then reducing data, presenting data, and drawing conclusions. The results showed that the son of An Nawawi Islamic boarding school Berjan Purworejo carried out the management of facilities and infrastructure in steps: planning carried out through program planning meetings at the An Nawawi male Islamic boarding school; Procurement was an activity of procuring pesantren facilities and infrastructure according the results of mutual agreement in the planning process; inventory, namely all items belonging to the An Nawawi men's boarding school are neatly inventoryed in the inventory list of goods; Maintenance, namely maintenance of facilities and infrastructure of An Nawawi men's boarding school, is carried out by all people who are in boarding schools. The controlling is carried out by the head of facilities and inscriptions section; The write-off is carried out at the An Nawawi men's boarding school by replacing if possible and removing from the inventory list of goods.